A Bridged-Switch Energy-Efficient Switching Scheme for Successive Approximation Register Analog-to-Digital Converters with a Low-Complexity Capacitor Drive Circuit - Yunfeng Hu; Bin Tang; Chaoyi Chen; Lexing Hu; Qingming Huang; Jiaqi Cai; Jinbo Xie; Bin Li; Zhaohui Wu (Applied Sciences, 2023)
In recent years, due to the rise of the Internet of Things (IoT), various sensors have come to be in great demand for IoT devices. Analog-to-digital converters (ADCs) act as an important part of receivers in sensors. To improve the uptime of IoT devices, a bridged-switch energy-efficient switching scheme for successive approximation register (SAR) ADCs with a low-complexity capacitor drive circuit is proposed. The technique of top-plate sampling and closed-loop charge recycling is used in the proposed switching scheme so that neither the first nor the second comparison consumes switching energy. The third comparison uses bridge switches to connect the subarray to the main array, effectively reducing switching’s energy consumption. Only the least significant bit (LSB) is dependent on the accuracy of Vcm; thus, the last comparison consumes little switching energy. The proposed switching scheme achieves an average switching energy value of 47.5 CV2ref, which is 96.52% lower than that of the conventional capacitor switching scheme and reduces the area by 75%. The other major circuit modules employed are bootstrapped switches, a fully dynamic comparator, and dynamic SAR logic. The proposed ADC was simulated under the conditions of 180 nm CMOS process and 1 MS/s, resulting in a 9.8-bit effective number of bits (ENOB), a signal-to-noise and distortion ratio (SNDR) of 60.76 dB, a spurious-free dynamic range (SFDR) of 69.85 dB, a power consumption of 14.7 μW, and a figure of merit (FoM) of 16.55 fJ/conv.-step.